School principal's strategy in shaping student character education in elementary school - Wilda Silvia; Siti Quratul Ain (Himpunan Pengembang Kurikulum Indonesia, 2025)
Character education is a fundamental aspect of the national education system, yet its implementation in elementary schools often faces serious challenges, including declining moral values, student discipline, and responsibility. This study aims to deeply analyze the principal's leadership strategies in shaping student character at SDN 011 Sorek 1, identify practical barriers in the field, and evaluate the contextual solutions applied. Employing a qualitative approach with a case study design, data were collected through semi-structured interviews, observations of school activities, and document analysis, then processed using the interactive model by Miles et al. The findings indicate that the principal implemented integrated strategies encompassing behavioral modeling of discipline, institutional planning within the vision and mission, habituation of daily routines, teacher competency training, and competition and recognition programs. Implementation obstacles included variations in student personalities, low responsibility for school facilities, and a lack of awareness of environmental cleanliness. These challenges were addressed through individualized guidance, strengthened teacher collaboration, and the internalization of a school culture rooted in religious values. This study concludes that the success of character education requires adaptive strategic leadership, consistent role-modeling by leaders, and active participation by the entire school community to create a moral environment conducive to student development. Abstrak Pendidikan karakter merupakan aspek fundamental dalam sistem pendidikan nasional, namun realitas implementasinya di sekolah dasar sering menghadapi kendala serius terkait penurunan moralitas, kedisiplinan, dan tanggung jawab murid. Penelitian ini bertujuan untuk menganalisis secara mendalam strategi kepemimpinan kepala sekolah dalam membentuk karakter murid di SDN 011 Sorek 1, mengidentifikasi hambatan praktis di lapangan, serta mengevaluasi solusi kontekstual yang diterapkan. Menggunakan pendekatan kualitatif dengan desain studi kasus, data dikumpulkan melalui wawancara semi-terstruktur, observasi aktivitas sekolah, dan analisis dokumen, yang kemudian diolah menggunakan model interaktif Miles et al. Temuan penelitian menunjukkan bahwa kepala sekolah menerapkan strategi terintegrasi yang mencakup keteladanan perilaku disiplin, perencanaan institusional dalam visi-misi, pembiasaan rutinitas harian, pelatihan kompetensi guru, serta program kompetisi dan penghargaan. Kendala implementasi meliputi variasi kepribadian murid, rendahnya tanggung jawab terhadap fasilitas sekolah, dan kurangnya kesadaran kebersihan lingkungan. Tantangan ini diatasi melalui pendekatan bimbingan individual, penguatan kerjasama guru, dan internalisasi budaya sekolah berbasis nilai religius. Penelitian ini menyimpulkan bahwa keberhasilan pendidikan karakter memerlukan kepemimpinan strategis yang adaptif, konsistensi keteladanan pimpinan, serta partisipasi aktif seluruh warga sekolah untuk menciptakan lingkungan moral yang kondusif bagi perkembangan murid. Kata Kunci: kepala sekolah; pelatihan sikap; pendidikan karakter; strategi